The Wonder of Water : Lived Experience, Policy, and Practice - Abram, David; Bannon, Bryan E.; Dicks, Henry; Donohoe, Janet; Gessas, Jeff; Glazebrook, Trish; Harding, Stephan; King, Sarah J.; Klaver, Irene J.; Lee Mueller, Martin; Leman Stefanovic, Ingrid; Leman, Dilys; et al. (University of Toronto Press, 2020)
Facing droughts, floods, and water security challenges, society is increasingly forced to develop new policies and practices to cope with the impacts of climate change. From taken-for-granted values and perceptions to embodied, existential modes of engaging our world, human perspectives impact decision-making and behaviour. The Wonder of Water explores how human experience - including our cultural paradigms, value systems, and personal biases - impacts decisions around water. In many ways, the volume expands on the growing field of water ethics to include questions around environmental aesthetics, psychology, and ontology. And yet this book is not simply for philosophers. On the contrary, a specific aim is to explore how more informed philosophical dialogue will lead to more insightful public policies and practices. Case studies describe specific architectural and planning decisions, fisheries policies, urban ecological restorations, and more. The overarching phenomenological perspective, however, means that these discussions emerge within a sensibility that recognizes the foundational significance of human embodiment, culture, language, worldviews, and, ultimately, moral attunement to place.